GOOD FINANCE GOVERNANCE MSMES THROUGH FINANCIAL PORTFOLIO METHOD AS BUSINESS SUSTAINABILITY EFFORT DURING THE COVID19 PANDEMIC - Dwi Dayanti Oktavia; Ike Ratnasari (Proceedings of the 1st International Conference on Social Science (ICSS), 2022)
Good financial governance is one of the keys for a business to survive and continue to thrive in any situation and condition. MSMEs are one of the largest contributors to national income and are able to increase economic growth in Indonesia, but many are still unaware of the importance of business financial governance. This is due to a lack of understanding related to financial governance as well as the difficulty of the financial governance process and the high costs that must be incurred if you use the services of a financial consultant. So that not a few SMEs who have difficulty maintaining their business. For this reason, a financial management method is needed that can help or facilitate MSME actors in managing their business finances so that they are able to continue to survive and be able to develop their businesses. The purpose of this research is to find outproblems faced by MSMEs related to business financial governance by utilizing the financial portfolio method so as to provide convenience for MSME actors in managing their finances so that they are able to provide quality financial information that is useful for MSMEs in managing their business..The research method used is the research method used in this study is a qualitative analysis with exploratory steps with participatory observation techniques. The data sources used are primary data in the form of observations and secondary data in the form of data collected, processed and presented by other parties in the form of books and the results of previous research related to MSME financial governance. Informants in this study are infinite. Based on the results of the study, it was found that the informants in financial management in general have been managed very well, this is evidenced by the recording of every financial transaction of the business being carried out. The management carried out by MSMEs is to make notes in the form of a financial portfolio